Effect of Child Labor and Performance on Child Relationship with Head in Rural Areas of Niger State, Nigeria - Alfa, Abdulmumini Baba; Abd Karim, Mohd Zaini (International Journal of Economics and Financial Issues, 2016)
In assessing the impact of child labour hours and educational performance on child relationship with head, an analytical model was developed based on the theories of Basu and Van (1998), and Fan (2011). Empirical data were obtained from Socio-Economic Survey (S-E-S) 2014, with a sample size of 845 primary school pupils ranging from 10 -14 years of age from 435 households in Suleja local government rural districts. The result from logit analysis shows that non-biological child engage in more hours of work than the biological child. Equally, children from the households that earn income below subsistence level work more hours, with negative impact on performance than those from households that earn income above subsistence. The use of extra-curricular activities social capital was therefore recommended to curb to reduce child participation in labour and enhance child school performance. Keywords: Labour, Performance, Foster, Income, Rural JEL Classifications: D10, J22, J23; J24; O15